Salvaged, Staged, and Safer Management of Aortoesophageal Fistula and Mediastinitis After Removing a Pork Bone: A Case Report - Ge, Yan; Tuerdi, Ayinuer; Yang, Xinming; Tang, Jingqun; Li, Quanming (Frontiers in Surgery, 2022)
Aortoesophageal fistula (AEF) caused by esophageal foreign body (EFB) ingestion is a life-threatening condition with a very low survival rate. However, the optimal management strategy remains undetermined. Here we describe our successful management of a patient with AEF and mediastinitis. A 36-year-old man developed persistent chest and back pain and vomited fresh blood 3 days after removal of a pork bone in the esophagus under endoscopy in a local hospital. Computed tomography (CT) confirmed bilateral pulmonary infections, mediastinitis, and fistula of the aortic arch. After a multidiscipline discussion, a comprehensive staged strategy was made including salvaged thoracic endovascular aortic repair (TEVAR) to control fatal bleeding, adequate mediastinal debridement, drainage with cervical incision, and video-assisted thoracoscopic surgery (VATS), as well as jejunostomy to avoid nasal or gastrostomy reflux to aggravate mediastinal infection. Furthermore, systematic personalized nutrition support and antibiotics were added. The patient recovered well and survived for 50 months till now. Careful assessment should be made with CT to make clear the risk of AEF before and after the removal of EFB. And a salvaged staged strategy of TEVAR with adequate mediastinal debridement and drainage in a less-invasive approach may be an alternative and safer management for those infected AEF patients caused by EFB.